A Post-Project Evaluation of an IT Service Management Improvement Project People and Tool - Mandingiado, Ralph Paolo; Imbang, Glen A. (Quezon City University of the Philippines Diliman, 2012)
Company ABC has recently concluded two major activities in its IT service improvement project : (1) the transition from an existing IT service desk provider to a new one and (2) the version upgrade of the existing IT service management tool. The scope of this post-project evaluation study of these two closely related activities to understand whether the projects' management were effective, achieved its objectives, and the outcomes had an impact. This post-project evaluation is a collection, record and information organization of results. This shall contain a report of short-term and immediate results from deliverables and observed and/or reported outcomes like behavioral, practice or policy changes borne from the project. This shall demonstrate the effectiveness, efficiency and proper use of organizational resources (i.e. financial, human, etc.), recognize actual changes and progress made, identify areas that were successful and those that need further improvement and finally, validate for project members and stakeholders that desired outcomes have indeed been achieved. The author postulates that project success be measured not only against the traditional triple constraint of cost, time and scope, and recommends that relevance and strategic fit, process compliance, deliverable, objectives and benefit realization and end user satisfaction with project management and output be considered as well. Recurring and key technology management issues on technology requirements gathering, resource availability and staff turnover, organizational structure and culture and technology decision making and current fit were identified and discussed. The author then recommends the creation of a standard project evaluation framework and standardization of definition of success and proposes a standard framework for process implementation projects. Finally, recommendations for future research such as post-project evaluation after a longer timeframe and business impact analysis and return on investment study was given.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Information Technology -- Management; IT Service Management